Effect of various synthesis parameters on the stability of size controlled green synthesis of silver nanoparticles. (12th April 2021) - Kaur, Ramanjeet; Avti, Pramod; Kumar, Vivek; Kumar, Rajesh
Abstract: In this study, we have focused on the green method using Litchi Chinensis Leaf Extract (LCLE) for the synthesis of silver nanoparticles (AgNPs). Here, the experimental control parameters (reducing/stabilizing agent quantity, reaction time and temperature, silver ion concentrations) were studied during the size controlled synthesis of silver nanoparticles and their physicochemical properties have been studied. For biological studies, the stability of AgNPs at physiological pH is of vital importance; hence, post-synthesis solution stability of AgNPs was examined at various pH conditions. Stable AgNPs are formed by treating the aqueous solution of AgNO3 with LCLE. Formation of AgNPs was observed visually by the change in the color and further characterized by the surface Plasmon resonance (SPR) peak observed at 436 nm by UV–vis spectroscopy. The synthesized AgNPs were also characterized for their size distribution by Dynamic Light Scattering (DLS), Scanning Electron Microscopy (SEM), Transmission electron microscope (TEM), crystalline nature by X-Ray Diffraction (XRD) and Fourier Transform infrared (FITR) for the functional groups present. The size of AgNPs was in the range of 40–50 nm, spherical in with face centered cubic (FCC) structure. The biomolecules (epicatechin) present in LCLE were responsible for reduction, capping, and stabilizing agent of AgNPs. Post- synthesis, the stability of AgNPs has been studied by changes in the SPR peaks at various pH (2–11) conditions using UV–vis spectroscopy. This size controlled nanoparticles are very stable at physiological pH and retain their intrinsic SPR property.